Managing Patient Factors in the Assessment of Swallowing via Telerehabilitation - Ward, Elizabeth C. (Hindawi Publishing Corporation, 2012)
Undoubtedly, the identification of patient suitability for a telerehabilitation assessment should be carried out on a case-by-case basis. However, at present there is minimal discussion of how telerehabilitation systems can accommodate and adapt to various patient factors, which may pose challenges to successful service delivery. The current study examines a subgroup of 10 patients who underwent an online assessment of their swallowing difficulties. Although all assessments were completed successfully; there were certain patient factors, which complicated the delivery of the online assessment session. The paper presents a discussion of the main patient factors observed in this cohort including the presence of speech and/or voice disorders, hearing impairment, dyskinesia, and behavioural and/or emotional issues and examines how the assessment session, the telerehabilitation system, and the staff involved were manipulated to accommodate these patient factors. In order for telerehabilitation systems to be more widely incorporated into routine clinical care, systems need to have the flexibility and design capabilities to adjust and accommodate for patients with varying levels of function and physical and psychological comorbidities.